2021
DOI: 10.1126/scitranslmed.abc2823
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of initial key steps of IL-17 receptor B oncogenic signaling for targeted therapy of pancreatic cancer

Abstract: The members of the interleukin-17 (IL-17) cytokine family and their receptors were identified decades ago. Unlike IL-17 receptor A (IL-17RA), which heterodimerizes with IL-17RB, IL-17RC, and IL-17RD and mediates proinflammatory gene expression, IL-17RB plays a distinct role in promoting tumor growth and metastasis upon stimulation with IL-17B. However, the molecular basis by which IL-17RB promotes oncogenesis is unknown. Here, we report that IL-17RB forms a homodimer and recruits mixed-lineage kinase 4 (MLK4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Another meaningful finding of this study was the correlation between MT1L and interleukins shown in our GSEA. Interleukin (IL)-17 is produced by a subset of T helper (Th) cells with a strong effect on immune cells and plays an essential role in cancer pathogenesis by directly or indirectly interacting with tumors [47]. Studies have confirmed that the change patterns of IL-17 expression might be associated with the infiltration of inflammatory cells, which might also contribute to the occurrence and development of BLCA [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Another meaningful finding of this study was the correlation between MT1L and interleukins shown in our GSEA. Interleukin (IL)-17 is produced by a subset of T helper (Th) cells with a strong effect on immune cells and plays an essential role in cancer pathogenesis by directly or indirectly interacting with tumors [47]. Studies have confirmed that the change patterns of IL-17 expression might be associated with the infiltration of inflammatory cells, which might also contribute to the occurrence and development of BLCA [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxia-inducible factor-1 alpha (HIF-1 α ) pathway is a crucial regulator of cellular adaptation of PC cells to hypoxia, and its abnormal activity may induce tumorigenesis and development of PC by promoting uncontrolled survival and growth, metabolic reprogramming, desmoplasia, immune evasion, autophagy, EMT, invasion and metastasis, stem-like tumorigenicity, angiogenesis, and radioresistance and chemoresistance of PC cells [ 157 , 158 ]. The IL-17 pathway accelerates tumorigenic and metastatic potential, and its activity serves as a predictor of PC prognosis and the efficacy of anticancer agents [ 159 – 162 ]. The Janus kinase (JAK)/STAT pathway is involved in carcinogenesis, development, growth, metastatic and angiogenic behaviors, immune surveillance, growth, stemness, anoikis resistance, EMT, treatment resistance, and invasion and migration of PC cells, while its activation is related to the reduced survival of patients with PC [ 115 121 , 163 , 164 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 Recently, it was found that IL‐17RB could play a special role in promoting tumor proliferation and metastasis. 23 The calcium signaling pathway is reportedly involved in the tumor microenvironment (TME) and resistance to some anti‐cancer drugs. 24 Accordingly, we hypothesize that LAMTOR3 can suppress KIRC progression by modulating these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%